Reflections from the Field: Ethical Challenges in Peacekeeping and Humanitarian Interventions - Last, Major D.M. (Tufts Archival Research Center, 2005)
Volume 24, Issue 1. Spring Having served as a United Nations peacekeeper in Cyprus, Croatia, Bosnia and West Africa and with NATO forces in Bosnia, Major David Last reflects on the ethical dilemmas confronting members of peacekeeping forces on the ground.